Aminocyanopyridines as anti‐lung cancer agents by inhibiting the STAT3 pathway. Issue 8 (8th May 2019) - Xu, Lingyuan; Qiu, Sensen; Yang, Lehe; Xu, Haitang; Liu, Xu; Fan, Shiqian; Cui, Ri; Fu, Weitao; Zhao, Chengguang; Shen, Liqun; Wang, Liangxing; Huang, Xiaoying
Abstract: Lung cancer is a leading cause of cancer‐related death worldwide. Cyanopyridines and aminocyanopyridines with carbon‐nitrogen bonds have been proved to exert significant anticancer, antibacterial, and anti‐inflammatory effects. In this study, we showed that aminocyanopyridine3o and3k displaying potent antitumor activity via inhibiting the signal transducer and activator of transcription 3 (STAT3) pathway. They blocked the constitutive STAT3 phosphorylation in a dose‐ and time‐dependent manner and regulated the transcription of STAT3 target genes encoding apoptosis factors. Most importantly, 3o also inhibited interleukin‐6‐induced STAT3 activation and nuclear localization. Furthermore, 3o significantly inhibited the tumor growth of H460‐derived xenografts. Taken together, these findings suggest that3o and 3k are promising therapeutic drug candidates for lung cancer by inhibiting persistent STAT3 signaling.